Evaluation of the Effects of High-Lysine Sorghum on Nursery Pig Performance - L. L. Thomas; R. D. Goodband; C. D. Espinosa; H. H. Stein; J. C. Woodworth; M. D. Tokach; S. S. Dritz; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2018)
Two experiments were conducted to determine the standardized ileal digestibility (SID) of amino acids in a high-lysine sorghum cultivar, followed by a growth trial to determine the effect of this sorghum on pig performance using increasing additions of feed-grade amino acids at the expense of soybean meal. In Exp. 1, ten growing barrows (initially 57.1 lb; Line 359 × 1050; PIC, Hendersonville, TN) were surgically fitted with a T-cannula at the terminal ileum and randomly assigned to 1 of 5 test diets in a 5-period, cross-over design. Experimental diets consisted of a corn-based diet, a diet containing high-lysine sorghum, or two diets with either white or red sorghum cultivars. The grain sources were the only protein sources included in these experimental diets. The fifth experimental diet was N-free for determining basal endogenous amino acid loss. All diets contained 0.40% chromic oxide as an indigestible marker. Standardized ileal digestible crude protein, lysine, methionine, threonine, and valine were greater (P<0.020) in corn than in the sorghum-based diets with no evidence for differences among the three sorghum cultivars. In Exp. 2, a total of 293 pigs (initially 21.3 lb; Line 241 × 600; DNA, Columbus, NE) were used in a 20-d growth trial. On d 20 after weaning, considered d 0 in the trial, pens were randomly assigned to 1 of 6 dietary treatments with 10 replications per treatment. Treatments consisted of a corn-based diet, a diet based on conventional sorghum (a mixture of red and white sorghum), and 4 diets with high-lysine sorghum. The corn-based, conventional sorghum, and the first high-lysine sorghum diets each contained the same amount of soybean meal with varying amounts of feed-grade amino acids. The 3 remaining high-lysine sorghum diets included incrementally increasing amounts of feed-grade amino acids, replacing soybean meal. Overall, there was no evidence for differences in average daily gain (ADG) or average daily feed intake (ADFI) among dietary treatments. However, pigs fed the high-lysine sorghum with the greatest amount of added feed-grade amino acids had the poorest feed-to-gain ratio (F/G) (P= 0.05) compared with those fed other experimental diets. In summary, SID amino acid values for the high-lysine sorghum used in this study were not different from either red or white sorghum cultivars; however, these values were all lower when compared with corn. When swine diets for nursery pigs were formulated on an SID amino acid basis, there were no differences in ADG among pigs fed any of the various diets. High-lysine sorghum is a viable alternative grain source in swine diets and can be used with feed-grade amino acids to reduce the amount of soybean meal in the diet, potentially lowering feed cost. Research is needed to determine the maximum inclusion of feed-grade amino acids in nursery pig diets without negatively impacting F/G.
Keywords: High-lysine sorghum; corn; feed-grade amino acids; nursery pigs